Isolation and identification of rhizospheric bacteria associated with lemongrass for potential bioremediation - Sanusi, Najwa Husna; Phang, Ing Chia; Nordin, Noor Faizul Hadry (Universiti Teknologi Malaysia, 2015)
Contamination of soil and groundwater pollution is a severe problem, has been attracting considerable public attention over the last decades. With the demand for green and cleaner technology for remediation process, there is an increased interest in moving away from conventional technologies towards bioremediation technologies. Rhizospheric zone is a suitable place for harboring bacteria that are capable to utilize chemical compounds which will be used either to facilitate growth of bacteria or the host plants. Identification of the specific microbial members should allow for better strategies to enhance biodegradation. This study aimed to isolate and identify the rhizospheric associated microbes of lemongrass (Cymbopogon citratus), a plant that commonly available in South East Asia, which could be used in future research on degradation studies of dibenzofuran. This probably is due to their ability to harbor large numbers of bacteria on their highly branched root systems. A total of 68 strains of dibenzofuran (DF)- degrading bacteria isolated from the rhizospheric soil of lemon grass from 2 different unpolluted sites were characterized. The isolates showed the ability to utilize dibenzofuran as the sole carbon and energy source up to 40 ppm. Identification of the isolates based on 16S rRNA gene sequence assigned them as members of the phyla Proteobacteria and Firmicutes, among which those of the genera, Proteobacteria were most abundant. The presented results indicated the potential of these bacterial isolates in bioremediation of dibenzofuran-contaminated soil.